Penyandang Disabilitas dalam Berpolitik Berdasarkan Hak Asasi Manusia - Muhammad Sholeh; Ferdinand Rafi Arya Putra; Daffa Andita Siswanto; Ahmad Fathir Alvian Maulana; Muhammad Abuhasan Assadzali (Perkara : Jurnal Ilmu Hukum dan Politik, 2023)
Humans are God's most noble creation, even though in their creation they have physical and mental differences between one another, which gives rise to advantages and disadvantages, but there are similarities, namely that they both have rights. The role of politics in the life of the nation and state cannot be separated from general elections which are carried out directly, publicly, freely, secretly, honestly and fairly. It is hoped that every citizen who meets certain requirements must exercise their right to vote. This includes people with disabilities who are still underestimated by society but have the right to vote and be elected. This research is normative or based on the norms of life of the Indonesian people themselves. Then this research uses several references from valid and trusted journals so that there is no data engineering in its creation. Apart from that, this research aims to open up public understanding regarding the importance of fulfilling political rights and obligations for people with disabilities, especially in general elections. Everyone has the right to determine who their chosen leader will be in the future. So this research is very necessary so that human rights violations do not occur especially in General Elections.